2011
DOI: 10.1007/s10661-011-2083-x
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning and sources of PAHs in wastewater receiving streams of Tianjin, China

Abstract: Polycyclic aromatic hydrocarbons (PAHs) partitioning among dissolved phase, suspended particulate matter, pore water, and sediment was studied in one moderately contaminated river (Yongding New River) and two highly contaminated drainage canals (South Drainage Canal and North Drainage Canal) of Tianjin, China. PAHs concentrations in sediment (ranged from 0.2 to 195 μg/g) showed positive relations with both total organic carbon contents (ranged from 0.7% to 31.1%, dw) and black carbon contents (ranged from 0.1%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 32 publications
(43 reference statements)
1
3
0
Order By: Relevance
“…The sorption of organic compounds to POC is related to the character of the POC, such as its chemical composition, molecular weight, solution chemistry, pore size distribution, surface chemistry, and pore structure (Kilduff et al, 1996;Wang et al, 2011); Low molecular weight organic compounds are most competitive, participating in direct competition with other high molecular weight organic compounds for adsorption sites (Quinlivan et al, 2005). This explains, in line with the findings of Wu et al (2011) and Qi et al (2012), why relatively low in situ logK OC values were found for high molecular weight PAHs in this study, as these PAHs did not adsorb as effectively onto particles when compared to low molecular weight PAHs.…”
Section: The Partition Between the Dissolved And Particulate Phasessupporting
confidence: 66%
See 1 more Smart Citation
“…The sorption of organic compounds to POC is related to the character of the POC, such as its chemical composition, molecular weight, solution chemistry, pore size distribution, surface chemistry, and pore structure (Kilduff et al, 1996;Wang et al, 2011); Low molecular weight organic compounds are most competitive, participating in direct competition with other high molecular weight organic compounds for adsorption sites (Quinlivan et al, 2005). This explains, in line with the findings of Wu et al (2011) and Qi et al (2012), why relatively low in situ logK OC values were found for high molecular weight PAHs in this study, as these PAHs did not adsorb as effectively onto particles when compared to low molecular weight PAHs.…”
Section: The Partition Between the Dissolved And Particulate Phasessupporting
confidence: 66%
“…]pyrene) showed poor agreement with the logK OC predicted from logK OW Wu et al (2011). found that K P decreased from five-ring to six-ring PAHs andQi et al (2012) also found that the logK OC of dibenzo[a,h]anthracene was lower than the logK OW from some samples collected in the field. Moreover, colloidal organic carbon has been reported to enhance organic contaminant concentration in the aqueous environment…”
mentioning
confidence: 92%
“…Overall, PAHs come from two major sources: fuel combustion (pyrolytic) or petroleum related material (petrogenic). Molecular ratios have been developed for interpreting PAH composition and determining their possible sources (Yunker et al 1996;Qi et al 2012). The abundance ratio of 2-3 ring hydrocarbons to 4-6 ring hydrocarbons ANT/(ANT+PHE), FLU/(FLU+PYR), InP/(InP+ BghiPL) and BaANT/BaANT+CHY are usually used.…”
Section: Diagnostic Ratiosmentioning
confidence: 99%
“…Polycyclic aromatic hydrocarbons (PAHs) partitioning among dissolved phase, suspended particulate matter, pore water, and sediment was studied in one moderately contaminated river (Yongding New River) and two highly contaminated drainage canals (South Drainage Canal and North Drainage Canal) of Tianjin, China (Qi et al, 2012). The PAH concentrations in sediment (ranged from 0.2 to 195 μg/g) showed positive correlation with both total organic carbon contents (ranged from 0.7% to 31.1%, dw) and black carbon contents (ranged from 0.1% to 2.1%, dw) in the sediments and most of the measured organic carbon normalized partition coefficients of PAHs in the three streams were 0.76 to 1.54 log units higher than the predicted values.…”
Section: Fate and Transportmentioning
confidence: 99%